2017
DOI: 10.1016/j.pmedr.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of sitting time over ten years in a large population-based Canadian sample: Findings from the Canadian Multicentre Osteoporosis Study (CaMos)

Abstract: Our objective was to describe patterns and predictors of sedentary behavior (sitting time) over 10 years among a large Canadian cohort. Data are from the Canadian Multicentre Osteoporosis Study, a prospective study of women and men randomly selected from the general population. Respondents reported socio-demographics, lifestyle behaviors and health outcomes in interviewer-administered questionnaires; weight and height were measured. Baseline data were collected between 1995 and 1997 (n = 9418; participation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…Reprinted with permission of Epidemiologic Reviews 24 . adequacy of energy intake for energy expenditure 44 , protein 45 , calcium and vitamin D 46 intakes, sedentary behavior 47 or physical activity 9 , adequacy of sleep and circadian rhythm 48 , and the psychosocial environment to rule out stress, threat, abuse, depression 49 and cognitive dietary restraint 21 (Figure 4). This section will discuss life phases before menopause during which cyclic progesterone may prevent osteoporosis.…”
Section: Progesterone For Prevention Of Bone Loss In Adolescent Pre-mentioning
confidence: 99%
“…Reprinted with permission of Epidemiologic Reviews 24 . adequacy of energy intake for energy expenditure 44 , protein 45 , calcium and vitamin D 46 intakes, sedentary behavior 47 or physical activity 9 , adequacy of sleep and circadian rhythm 48 , and the psychosocial environment to rule out stress, threat, abuse, depression 49 and cognitive dietary restraint 21 (Figure 4). This section will discuss life phases before menopause during which cyclic progesterone may prevent osteoporosis.…”
Section: Progesterone For Prevention Of Bone Loss In Adolescent Pre-mentioning
confidence: 99%
“…Some reviews have summarized the plurality of potential influences on sedentary behavior, including TVtime. [19][20][21][22] Furthermore, few longitudinal studies have revealed the patterns and predictors of sitting time throughout adulthood, 23,24 suggesting that several factors and life events (eg, male gender, higher education, full-time employment, staying obese, and consistently low physical activity levels, and changing jobs, retiring, or illness) contribute to high sitting levels. Divergent associations were identified for different aged groups for women.…”
Section: Introductionmentioning
confidence: 99%
“…Schooling was positively related to TST in this study. Other papers also found a positive association between schooling and sitting time 26 , as well as physical activity 24 . Namely, individuals with higher schooling are among the most exposed to sedentary behavior and the most physically active ones.…”
Section: Discussionmentioning
confidence: 87%